2020
DOI: 10.1016/j.childyouth.2020.105466
|View full text |Cite
|
Sign up to set email alerts
|

Stressors of COVID-19 and stress consequences: The mediating role of rumination and the moderating role of psychological support

Abstract: Highlights Stressors from COVID-19 was positively related to onset of stress-consequences. Stressors from COVID-19 was positively related to engagement in rumination. Rumination mediated the link between stressors of COVID-19 and stress-consequences. Psychological support buffered the effect of COVID-19 stressors on rumination. Psychological support buffered the effect of rumination on stress-consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 54 publications
7
102
0
3
Order By: Relevance
“…In line with previous studies, 21,30,31,40,41 perceived social support was negatively associated with psychological distress and predicted an incrementally significant variance, even when subjective severity and different types of rumination were jointly considered. This finding suggests that perceived social support could mitigate the negative consequences of psychological distress during the COVID-19 crisis.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies, 21,30,31,40,41 perceived social support was negatively associated with psychological distress and predicted an incrementally significant variance, even when subjective severity and different types of rumination were jointly considered. This finding suggests that perceived social support could mitigate the negative consequences of psychological distress during the COVID-19 crisis.…”
Section: Discussionsupporting
confidence: 90%
“…As rumination hinders adaptive problem-solving (21) and induces greater hopelessness (20), individuals may further lose the motivation to tackle the source of the issue, resulting in prolonged depressive symptoms (22). Early evidence of the role of rumination on stress consequences amid the COVID-19 pandemic has generally supported prior findings [e.g., (3,23)]. However, these studies have measured general ruminative tendencies within the individual.…”
Section: Epidemic Rumination and Depressionmentioning
confidence: 66%
“…Such public health measures have led to a downstream torrent of negative mental health outcomes. Indeed, several studies have found that COVID-19 related stressors accrued a myriad of negative effects on mental health, such as inducing symptoms of both anxiety and depression [e.g., ( 1 3 )].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, stressors associated with COVID-19 activated individuals' rumination mechanisms, which may have an impact on individual creativity. It has been shown that a higher frequency of rumination during the pandemic resulted in more negative emotions and decreased cognitive function (Newman et al, 2018;Ye et al, 2020), which is detrimental to the development of creative thinking. However, individuals can also increase their self-confidence by recalling positive examples through rumination (Bandura, 1997).…”
Section: Introductionmentioning
confidence: 99%